A design document generator to support a linkage between code and document - Izzul Hidayat Naisan, 1984-; Suhaimi Ibrahim, supervisor; Fakulti Komputeran (2010)
Thesis (Sarjana Sains (Sains Komputer)) - Universiti Teknologi Malaysia, 2010